Practicality Analysis of Project-Based Learning Electronic Modules to Facilitate Students' Creative Thinking Skills with the Help of the Heyzine Application on Climate Change Material - M Ilham; Dea Stivani Suherman; Ratnawulan Ratnawulan; Fadhila Ulfa Jhora (Department of Physics Universitas Negeri Padang, 2026)
21st-century learning is often associated with the term 4C skills: critical thinking, creativity, collaboration, and communication. Creative thinking is one of the skills that students must have in 21st-century learning. Based on a preliminary study, it was found that students' creative thinking skills are still in the very low category, especially on climate change material. This needs to be followed up for student success in 21st-century learning. One alternative solution that might be able to overcome this problem is to develop teaching materials in the form of project-based electronic modules to facilitate students' creative thinking skills on climate change material. The purpose of this study was to determine the practicality of project-based electronic modules to facilitate students' creative thinking skills on climate change material by teachers and students. This study used the Research and Development (R&D) method with a 4D development model limited to the development stage, which includes definition, design, and development. The object of this study was a project-based electronic module. Data collection in this study was validity measurement data by three experts from UNP and practicality measurement data by teachers and students. The data obtained were then analyzed using validity analysis techniques with Moment Kappa (k) and product practicality analysis. The results of the validity assessment of the electronic module based on project-based learning obtained a score of 0.87 in the very valid category. Furthermore, the results of the practicality assessment of the electronic module based on project-based learning by teachers with an average score (0.9) and students obtained an average score (0.91). The results of this study indicate that the electronic module based on project-based learning to facilitate students' creative thinking abilities assisted by the heyzine application on the climate change material developed is very valid and very practical to use in the physics learning process, especially on climate change material.